Toksisitas Akut dan Subkronis Ramuan Ekstrak Kelor dan Klabet sebagai Pelancar ASI dan Penambah Gizi - Widowati, Lucie; Winarno, M Wien; Intan, Putri Reno (Jurnal Kefarmasian Indonesia, 2014)
Insufficient breast milk intake from a mother to their babies may cause a poor infant growth. We have conducted a research on mixture of klabet seed extracts (Trigonella foenum-graecum L.) and kelor leaf extract (Moringa oleifera Lamk.) (1:1) for increasing breast milk production in nursing mothers and nutritional supplement for infants. The study is a completely randomized design. We used white rats (Rattus novergicus), Wistar strain, as many as 50, that were divided into 5 dose groups for the acute toxicity testing and 40 rats in 4 dose groups for the sub-chronic toxicity testing.The acute toxicity testing of fenugreek seed extracts and moringa leaf extracts (1:1) results in a pseudo value LD50 >4,000 mg/200g bw, therefore we classified the materials to practically non-toxic (PNT). For the subchronic toxicity testing, the result showed a normal state on liver and kidney function.